Pemberian Oksigen Dan Posisi Semi Flower Dalam Mengatasi Gangguan Pola Napas Pada Pasien Nstemi Rsud Waled Kabupaten Cirebon - Lalu Rahmatullah Hidayat; Ahmad Syaripudin; Pujiyana; Ira Rahayu Okta; Herlina (Awatara Publisher, 2024)
NSTEMI is a clinical syndrome resulting from blockage of coronary arteries, either intermittent or permanent due to rupture of atherosclerotic plaque. NSTEMI is usually caused by severe narrowing of the coronary arteries and blockage of the coronary arteries is characterized by chest pain and shortness of breath, thereby reducing oxygen saturation and increasing the respiratory rate. Data (World Health Organization, 2018) shows that the incidence of ST elevation Mycardial Infaction (STEMI) is decreasing, while the incidence of Non-ST Elevation Mycardial Infaction is increasing. Data shows that 5 million people experience STEMI, and 4 million people experience NSTEMI. Objective: This study is to determine the application of giving the semi-Fowler position and oxygen to NSTEMI patients at Waled Hospital, Cirebon. Method: The method used in this writing is a case study using a nursing process approach to 1 Non ST Elevation Myocardial Infarction (N-STEMI) patient. Results: The results of the application showed that before being given the semi-Fowler position and oxygen, the oxygen saturation was 94% and the respiratory rate was 25x/minute in the abnormal category. Meanwhile, after applying the semi-fowler's position and oxygen, the patient's respiratory rate decreased by 16-20x/minute and oxygen saturation was 97%-99% in the normal category. Conclusion: The results of the application after being given the semi-fowler's position and oxygen to the patient showed an increase in oxygen saturation and decreased respiratory rate